Evaluation of the functional properties of microcrystalline chitin from blue crab shells (Callinectes sapids) - Barracoso, Ma. Barba Anne C.
Microcrystalline chitin, prepared from a laboratory extraction of crude chitin (poly-β (1->4)-N-acetyl-D-glucosamine) was compared against microcrystalline cellulose to examine the potential use of cellulose-like biopolymers as functional additives for use in food formulations. Water and fat binding capacities, emulsification properties and bulk density were evaluated. A chitin yield level of 35.9% (dry basis) was obtained from the process employed in the isolation of chitin from shells of Blue crabs (Callinectes sapidus). Chemical analyses show that the crude chitin has 2.40% crude nitrogen content, 0.21% ash content, 0.31% fat content and moisture content of 7.20% (db). The crude chitin has a coarse, grainy texture and slightly pink in color. The microcrystalline prepared from the previously isolated crude chitin has a flaky texture and opaque white in color. The conversion process yielded 66.7% microcrystalline chitin. Freeze drying of the material gave the product a final moisture content of 8.76% (db). Results of the functional tests showed that microscrystalline chitin exhibited superior functional characteristics than microscrytalline cellulose. Water binding capacity for microcrystalline chitin had a mean value of 654.82% (w/w) and fat binding capacity at 8.27.69% (w/w). Microcrystalline cellulose did not produce emulsions but microcrystalline chitin showed emulsifying properties with an average emulsifying capacity of 25%. Similarly, microcrystalline chitin was bale to stabilize emulsions during heat treatments. Bulk density tests revealed that microcrystalline cellulose had higher bulk density compared to that of microcrystalline chitin.